Criteria for risk assessment of plants produced by targeted mutagenesis, cisgenesis and intragenesis. (20th October 2022) - ; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: EFSA was asked by the european Commission to develop criteria as advice for consideration for the risk assessment of plants produced by targeted mutagenesis, cisgenesis and intragenesis. EFSA proposes in this statement six main criteria to assist the risk assessment of these plants. The first four criteria are related to the molecular characterisation of the genetic modification introduced in the recipient plant. The four criteria evaluate whether any exogenous DNA sequence(s) is/are present (Criterion 1), whether such sequence derives from the breeders' gene pool (Criterion 2), the type of integration (Criterion 3) and whether any endogenous plant gene is interrupted (Criterion 4). Depending on the evaluation of the above criteria, the product can be a genome edited plant where no exogenous DNA sequence is present, or a cisgenic or intragenic plant where the cisgenic and intragenic sequence are introduced by targeted insertion and no plant endogenous genes are interrupted. In these cases, two more criteria are assessed to evaluate the history of safe use (Criterion 5) and the structure and function of the new allele (Criterion 6). If cisgenic and intragenic sequence are introduced by random integration without interruption of an endogenous gene, or when no risk is identified when an endogenous gene is interrupted, the criteria 5 and 6 will also be assessed. Evaluating the history of safe use is an important part of the proportionate risk assessment of cisgenic, intragenic and genome‐edited plants since the newly introduced allele may already be present in nature. However, when the history of safe use cannot be sufficiently demonstrated, the function and structure of the introduced allele should be carefully assessed. Recommendations are also included on the aspects that need further elaboration for full applicability of the criteria proposed herein are also included. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2022.7621/full